Adaptation of Chronic Otitis Media Questionnaire (COMQ-12): reability and validity of the Indonesian version - Sudrajad, Hadi; Hendradewi, Sarwastuti; Primadewi, Novi; Kandhi, Putu Wijaya; Seytopambudi, Kukuh (PERHATI-KL, 2024)
Background: Chronic suppurative otitis media (CSOM) is one of the most common ear diseases that has a major impact on quality of life (QoL). The Chronic Otitis Media Questionnaire 12 (COMQ-12) is a CSOM-specific questionnaire that aims to assess QoL. Until currently, there is no questionnaire that has been tested for reliability and validity in the Indonesian version. Purpose: To assess the reliability and validity of the Indonesian version of COMQ-12. Method: An analytic observational study with a cross-sectional design, conducted in Dr. Moewardi General Hospital Surakarta Indonesia from March to May 2024. Reliability was assessed by internal consistency, and validity was assessed by Pearson correlation. Result: The reliability test with internal consistency obtained Cronbach’s alpha value for all question items >0.7. This indicated that all question items had good reliability. Meanwhile, the validity test with the Pearson correlation test obtained a p-value <0.05 for all question items with coefficients, all of which were positive. This indicated that all question items had good validity. Conclusion: Indonesian version of COMQ-12 has good reliability and validity to assess QoL in CSOM patients. Keywords: CSOM, COMQ-12, QoL, reliability, validity ABSTRAK Latar belakang: Otitis media supuratif kronik (OMSK) merupakan salah satu penyakit telinga yang paling umum dijumpai, dan berdampak besar pada kualitas hidup (QoL). Kuesioner Otitis Media Kronik 12 (COMQ-12) merupakan kuesioner khusus Otitis Media Supuratif Kronik (OMSK) yang bertujuan untuk menilai QoL, namun saat ini kuesioner COMQ-12 dalam versi Bahasa Indonesia belum teruji reliabilitas dan validitasnya. Tujuan: Untuk menilai reliabilitas dan validitas COMQ- 12 versi Bahasa Indonesia. Metode: Penelitian observasi analitik dengan desain potong lintang, yang dilakukan di RSUD Dr. Moewardi Surakarta, Indonesia dari bulan Maret sampai Mei 2024. Reliabilitas dinilai dengan konsistensi internal, dan validitas dinilai dengan korelasi Pearson. Hasil: Uji reliabilitas dengan konsistensi internal memperoleh nilai Cronbach’s alpha untuk semua butir soal >0,7. Hal ini menunjukkan bahwa semua butir soal memiliki reliabilitas yang baik. Sementara itu, uji validitas dengan uji Pearson correlation memperoleh nilai p<0,05 untuk semua butir soal, dengan koefisien yang semuanya positif. Hal ini menunjukkan bahwa semua butir soal memiliki validitas yang baik. Kesimpulan: COMQ-12 versi Indonesia mempunyai reliabilitas dan validitas yang baik untuk menilai kualitas hidup pasien OMSK.